2016
DOI: 10.1071/rd15184
|View full text |Cite
|
Sign up to set email alerts
|

Distribution pattern of cytoplasmic organelles, spindle integrity, oxidative stress, octamer-binding transcription factor 4 (Oct4) expression and developmental potential of oocytes following multiple superovulation

Abstract: The aim of the present study was to determine the effects of repeated superovulation on oocyte quality and embryo developmental potential. Female Swiss albino mice were injected with 5IU pregnant mare's serum gonadotropin followed 48h by 10IU human chorionic gonadotropin. Mice were superovulated up to four times with a gap of 7 days between each superovulation cycle. Ovarian weight increased significantly with an increasing number of superovulation cycles. Although the first stimulation cycle resulted in a thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 46 publications
1
37
0
Order By: Relevance
“…While superovulation treatment has become the basic methodology of human and animal ART programs, it has been reported that decreased quality of superovulated oocytes before and after IVF resulted the reduced fecundity. Increased preimplantation mortality after superovulation has been reported in mice ( Beaumont and Smith, 1975 ; Ertzeid and Storeng, 1992 ; Kalthur et al, 2015 ) and rats ( Miller and Armstrong, 1981 ). Ovarian hyperstimulation can increase chromosomal abnormalities in murine embryos ( Elbling and Colot, 1985 ; Huffman et al, 2015 ; Luckett and Mukherjee, 1986 ; Ozturk et al, 2016 ), and mitochondrial deformity further induced oocyte aneuploidy ( Plachot, 2003 ; Takeuchi et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…While superovulation treatment has become the basic methodology of human and animal ART programs, it has been reported that decreased quality of superovulated oocytes before and after IVF resulted the reduced fecundity. Increased preimplantation mortality after superovulation has been reported in mice ( Beaumont and Smith, 1975 ; Ertzeid and Storeng, 1992 ; Kalthur et al, 2015 ) and rats ( Miller and Armstrong, 1981 ). Ovarian hyperstimulation can increase chromosomal abnormalities in murine embryos ( Elbling and Colot, 1985 ; Huffman et al, 2015 ; Luckett and Mukherjee, 1986 ; Ozturk et al, 2016 ), and mitochondrial deformity further induced oocyte aneuploidy ( Plachot, 2003 ; Takeuchi et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, repeated superovulation affects ovarian structure and function in rhesus monkeys 13 . Multiple superovulation phases changed the organelle distribution in mouse oocytes 14 . These data indicate that repeated superovulation reduces oocyte quality, but the mechanism remains unclear.…”
mentioning
confidence: 98%
“…**p < 0.01, ***p < 0.001. 5mc: 5-methylcytosine [Color figure can be viewed at wileyonlinelibrary.com] Albertini, 2003; Kalthur et al, 2016;Xie et al, 2016). By using a murine model, we found that repeated superovulation reduces oocyte quality by disrupting meiotic cytoskeletal assemblies, mitochondrial function, and genomic DNA methylation; elevating oocyte apoptosis; and inducing oxidative stress.…”
Section: Discussionmentioning
confidence: 93%